Private Sector Export to Emerging Market Economies During Times of Crisis: How Can Export Credit Agencies Help? - Trung Quang DINH; Hilmar Þór HILMARSSON (Revista de Management Comparat International, 2012)
In an increasingly globalized world, economic growth depends much on openness of economies and trade among nations. The current economic and financial crisis has severely affected trade flows in the world that dropped sharply in the second half of 2008 and 2009. During the crisis, export credit agencies (ECAs) have played an increasing role in maintaining and stimulating cross border trade to emerging market economies. The article discusses the role and risk mitigation instruments of ECAs. It also provides examples of cross border trade and illustrates how the instruments of ECAs have been applied in real world situations to mitigate against commercial and non-commercial/political risks in emerging market economies.